Levels of editorial analysis and criticism of speech - Zhauniarovich, Piotr P. (Journal of the Belarusian State University. Journalism, 2020)
The article deals with the current state of editorial analysis in mass media and publishing. Changes in the information space of the Republic of Belarus over the past 25 years set new challenges for editors. These challenges are the result of changes in the type of authors’ materials and the way of their delivery to the customer. The text becomes an information and spiritual product and like any product should be sold for profit. The increase of the visual component in media reports indicates that as in the product the packaging,the outer shell that can hide poor quality content is dominating now. The essence of editorial analysis is to determine the degree of perlocutive effect, which should be predicted and, if necessary, enhance its positive component. The selection of macro and micro level of editorial analysis is dictated by the need for differentiation of editorial actions: in the first case, the text is evaluated as an integral structure, in the second case – as a sum of its components. The result of editorial analysis at the macro level is acceptance or rejection of the proposed media product, and the result of editorial analysis at the micro level is bringing the accepted material to the condition in which the consumer will get the effect programmed by the author. However, all actions performed by the editor are carried out before the publication of the work. This is the difference between editorial analysis and the criticism of speech – a set of actions taken by a researcher of already published work. The replacement of the term «editing» (or «literary editing») by a combination «criticism of speech» destroys the established terminology apparatus of editing as a complex scientific field, as its important element – editorial editing, intended to reduce the gap between the real result of reading the author’s material and the result that fully expresses the author’s thought and influences the consumer of the media product – is lost. The increase of the editor’s theoretical competences will minimise possible setbacks of a particular mass media or publishing house.
Keywords: editing; editorial analysis; macro level and micro level of editorial analysis; criticism of speech